Rumah Restorative Justice Kecamatan Socah-Bangkalan Madura Sebagai Media Penghubung Solutif Pada Fenomena Pelaku Balapan Motor Liar Usia Anak Dibawah Umur - Rohma Safitri (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
The social environment will have a significant influence on the growth of adolescence, especially in this illegal racing action, teenagers have a thirst for high curiosity, juvenile delinquency and are influenced by the actions of a friend or just want to be called a winner in a wild racing event. Illegal racing is an activity where vehicles, both motorcycles and cars, compete on a public track with the potential to experience traffic accidents. Even though illegal racing activities have been carried out many times by the authorities and enforced, in fact, until now illegal racing is still often carried out. This study aims to find out whether the Restorative Justice House in Socah-Bangkalan Madura District as a liaison media for solving solutions to victims and perpetrators as well as educating media for the community in some of the problems that occur, can work effectively against the phenomenon of illegal racers in children aged 10-17 year. In this case, I include the research location of the Restorative Justice House, Socah-Bangkalan, Madura District. Keywords: Teenagers, Wild Racing, Juvenile Criminal Law and Restorative Justice